Dari Pengabdian Kecil, untuk Dampak yang Lebih Besar: Anak-Anak dalam Pemilahan Sampah - Sunardi, Kartika Setyaningsih; Purwanti, Ratih (Jurnal Pengabdian Masyarakat Permata Indonesia, 2025)
This community service aims to increase the awareness of children aged 4-14 years in the Al-Qur'an Education Park (TPA) about waste sorting as a solution to environmental problems in Indonesia, where waste production reaches 68 million tons per year with suboptimal management. With the integration of Islamic values, this activity supports the formation of an environmentally friendly generation and contributes to the Sustainable Development Goals (SDGs) point 12. The implementation method uses an interactive approach at two landfill locations in Condongcatur, Sleman (Raoudlotul Jannah Mosque Landfill on September 8, 2025 and Gandok Mulia Mosque Landfill on September 13, 2025), including lectures, questions and answers, singing, games with prizes, and direct practice of sorting organic, inorganic, and B3 waste. The activity was attended by 57 participants with high participation (90% enthusiasm) and effective in forming environmentally friendly behavior. The discussion confirmed that this approach is more effective than the passive method, with the potential for replication to reduce plastic waste by up to 20-30%. The conclusion affirms the success of the activity as an educational model at the TPA, with suggestions for follow-up, age differentiation, and stakeholder collaboration.